Epidemiology of hepatitis C virus in lymphomas (Hematology Meeting Reports, 2009)
Hepatitis C virus (HCV) is an RNA virus and is a member of the Flaviviridae family. It is the most common cause of sporadic non-A non-B and post-transfusion hepatitis (Kuo et al, 1989) and a major cause of chronic liver diseases, including liver cirrhosis and hepatocellular carcinoma. In addition to the direct liver injury, various extrahepatic manifestations includine autoimmune disorders, glomerular injury, vasculitis, sicca syndrome, and type-II cryoglobulinemia (MCII) may occur in these patients. MCII is a systemic vasculitis often characterized as “benign” B-cell proliferation that evolves into B-cell non-Hodgkin lymphoma (B-NHL) in 8-10% of affected cases. An estimated 40-100% of patients with MCII are chronically infected with HCV (Agnello et al, 1992; Pozzato et al, 1994). This finding led to the hypothesis that HCV may play a role in lymphomagenesis, and several studies have investigated the potential association between HCV infection and B-NHL, whether related or not to MCII. Results of these studies have been conflicting.